KERJASAMA PEMERINTAH DENGAN PIHAK SWASTA, MASYARAKAT DAN ANTAR PEMERINTAH DALAM PENANGANAN PENCEMARAN LIMBAH BATIK DI KOTA PEKALONGAN PADA TAHUN 2015 - Ayu Cavandhes Cahyaningtyas; Teguh Yuwono; Priyatno Harsasto (Journal of Politic and Government Studies, 2017)
Batik industry is an industry that many exist in Pekalongan city, the existence of batik industry are produces waste from the process of making batik. There are two possibilities to dispose the batik waste, there are processed first and diposed directly without processing that will cause pollution. The purpose of this research are to identify the patterns of inter-governmental cooperation, and government with private and community in overcoming the problem of batik waste pollution, and to know the success rate ofcooperation patterns that has been done to overcome the problem of batik waste pollution.The method of the research is used qualitative approach with data collection technique that consist of observation, interview, and documentation. Informants in this research are head of Environmental Section and Environmental Law Arrangement of Environmental Department (DLH) Pekalongan city, Head of Pollution Control and  Damage Section of DLH Pekalongan city, Head of waste pollution control section of DLH Pekalongan city, the private sector there is batik craftsmen, and the community there is environmental care community.The result of the study indicate that 1) The pattern of inter-governmental cooperation is for funding the manufacture of IPAL, 2) The pattern of government cooperation with the privat sector (batik craftsmen) is divison the authority, that is government facilitates the construction of IPAL and provides land, whereas batik craftsmen are obliged to maintain and operate the IPAL, 3) The pattern of government cooperation with the community is the community independently provide assistance for the construction of IPAL, while the government did the coaching, supervision, assistances, and providing moral support. 4) The implementation of cooperation in overcoming the pollution of batik wate in Pekalongan city has not effectively. Keywords : Cooperation, Pollution of Batik Waste